2022
DOI: 10.1002/wsb.1325
|View full text |Cite
|
Sign up to set email alerts
|

Density from pellet groups: Comparing methods for estimating dung persistence time

Abstract: Effective wildlife management often relies on estimates of animal density, and cue counting is a viable estimation strategy.A key component of density estimation from dung, a form of cue counting, is estimation of the persistence time, t ^, of dung piles. However, differences between observers on what constitutes a dung pile may alter subsequent density estimates.Additionally, many researchers studying white-tailed deer (Odocoileus virginianus) have substituted for t ^the number of days between the date in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 47 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…Indeed, concordance between our two viewers dropped to as low as 30% in areas that did not have snow cover, regardless of detection history, even though both viewers had undergone extensive training to examine IR video that we captured from aerial platforms. Other studies have reported lack of concordance between the classifications of multiple viewers of both aerial video (Beaver et al, 2020;Preston et al, 2021) and other types of population data (Delisle et al, 2022). In instances when high certainty cannot be obtained due to the natural history of the target species (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, concordance between our two viewers dropped to as low as 30% in areas that did not have snow cover, regardless of detection history, even though both viewers had undergone extensive training to examine IR video that we captured from aerial platforms. Other studies have reported lack of concordance between the classifications of multiple viewers of both aerial video (Beaver et al, 2020;Preston et al, 2021) and other types of population data (Delisle et al, 2022). In instances when high certainty cannot be obtained due to the natural history of the target species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We sampled deer populations in Indiana's Deer Regional Management Units 3, 4 and 9 (Delisle et al., 2022; Swihart et al., 2020). We surveyed two different 6.4 × 6.4‐km areas within each Regional Management Unit (hereafter, RMU), resulting in six total areas flown (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we used a weighted habitat‐specific persistence rate for each RMU, with weights based on the sampling effort in each habitat type in each sub‐area (Estimation of persistence, available in Supporting Information). We used the same defecation rate of 26.8 fecal‐pellet groups/deer/day for density estimates in each RMU (Delisle et al 2022 b ). We included variation from the persistence rate but not the defecation rate in the final density estimates from pellet sampling because we did not experimentally estimate the defecation rate.…”
Section: Methodsmentioning
confidence: 99%
“…We included variation from the persistence rate but not the defecation rate in the final density estimates from pellet sampling because we did not experimentally estimate the defecation rate. Instead, we used the defecation rate from previous research in similar study areas (Delisle et al 2022 b ). Similarly, to model the detection process and select a final model, we used the methods in Delisle et al (2022 b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation